'Comparable to MTV – but Better': The Impact of The Chart Show on British Music Video Culture, 1986–1998. Issue 1 (July 2017) - Smith, Justin
Abstract : The Chart Show was a weekly UK TV programme showcasing music videos from the Media Research Information Bureau (MRIB) Network Chart and a range of independent and specialist pop music charts. It began broadcasting on Friday evenings on Channel 4 in April 1986 and ran for three series until September 1988. Its production company, Video Visuals, subsequently found a new home for The Chart Show with Yorkshire Television on ITV, where it went out on Saturday mornings between January 1989 and August 1998. What made the show unique in the British broadcasting context was that it was the first presenter-less pop chart programme that showcased popular music exclusively in video form. Beginning at a time when MTV was still unavailable in the UK, The Chart Show was innovatory in consolidating music video as the lingua franca of the pop singles market. Drawing on archival sources from Channel 4, and the trade and popular music presses, this article shows how The Chart Show helped shape the form of music video, contributed to its commercial status, boosted singles sales, and drove industry demand and production schedules. It argues that an appreciation of music video is dependent upon the historical specificity of its broadcast context. This article was published open access under a CC BY licensehttps://creativecommons.org/licenses/by/4.0/